Reduced voltage stress hybrid multilevel inverter using optimised predictive control - Khandelwal Y.; Routray A.; Singh R.K.; Mahanty R. (My University, 2025)
This study presents a hybrid multilevel inverter (HMLI), capable of generating 19 voltage levels using a single DC voltage source. The peak inverse voltage of all the switches is restrained within the input DC source voltage in the proposed HMLI, which requires only three capacitors and 15 switches to achieve 19 voltage levels. In the proposed HMLI, one of the capacitors is self-balanced, while the other two capacitors are balanced using a modified finite control set model predictive control (MFCS-MPC). The proposed MFCS-MPC reduces the computation time considerably without affecting the performance of the system. The proposed HMLI is compared with some other HMLI topologies to show its merits in terms of active and passive components. Finally, the steady-state and dynamic performance of the proposed topology and its control algorithm is validated through simulation and experimentation for a 1 kW prototype. © 2020 Institution of Engineering and Technology. All rights reserved.